The art of serendipity: killing of Caenorhabditis elegans by human pathogens as a model of bacterial and fungal pathogenesis. Issue 1 (1st June 2003) - Mylonakis, Eleftherios; Ausubel, Frederick M; Tang, Robin Jian; Calderwood, Stephen B
The nematode worm, Caenorhabditis elegans, has been used to develop a facile model system of host––pathogen interactions to identify basic evolutionarily conserved pathways associated with microbial pathogenesis. The model involves the killing of Caenorhabditis elegans by a variety of human pathogens. Several virulence-related genes in a variety of pathogens previously shown to be involved in mammalian infection have also been shown to play a role in Caenorhabditis elegans killing. Screening of large numbers of microbial mutants for attenuation in a mammalian model would require thousands of mice, rats or rabbits. In contrast, the Caenorhabditis elegans model allows rapid identification of mutants in microbial genes associated with pathogenesis and then these phenotypes can be confirmed in a relevant mammalian model.